1976
DOI: 10.3109/17453677608998980
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Restoration of Muscle Strength After Intramedullary Nailing of Fractures of the Femoral Shaft

Abstract: The maximal isometric muscle strength of hip abduction, knee extension and knee flexion was measured in 23 patients operated on for femur diaphyseal fractures and fitted with a stable intramedullary Kiintscher nail after reaming of the medullary cavity. The trauma, the immobilization and the surgery influenced the musculature of the operated as well as the intact leg. The muscle power recovered in a couple of years, but even after 2-6 years a significantly reduced power was found in the knee extensors, and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 2 publications
1
10
0
1
Order By: Relevance
“…As with other authors, we have found a slight increase in the strength of the uninjured limb with time 4 with improvement of up to 25% being noted, but this increase tended to reach a plateau early. Our study also confirmed that there is a high correlation between peak torque, total work and mean power between the two test speeds.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…As with other authors, we have found a slight increase in the strength of the uninjured limb with time 4 with improvement of up to 25% being noted, but this increase tended to reach a plateau early. Our study also confirmed that there is a high correlation between peak torque, total work and mean power between the two test speeds.…”
Section: Discussionsupporting
confidence: 62%
“…There have been few reports on the recovery of muscle strength after fractures of the lower limb. Of these, most have been concerned with muscle recovery after fractures of the femur rather than of the tibia, [1][2][3][4] but the latter are much more common and tend to affect younger patients, many of whom are keen to return to sports and other activities. 5 We have examined the recovery of muscle groups of the lower limb after fracture of the tibial diaphysis with particular reference to the age of the patient, the mechanism of injury and the type of fracture.…”
mentioning
confidence: 99%
“…In addition, this technique requires inevitable surgical dissection through the hip abductor and exorotator muscles and, last but not least, at implant removal, major surgical tissue dissection may cause considerable problems. The above outlined problems may, ultimately, result in reduced daily function accompanied by residual pain, stiffness, muscle weakness with discrete Duchenne limp, and some loss of endurance [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Another series of 32 patients with femoral fractures had 41% of patients with trochanteric pain and high incidences of abductor weakness and functional deficits. Hip abductor weakness may persist for as much as 2 years [6]. A cadaveric nailing study showed substantial soft tissue damage occurred when using traditional entry sites [8].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, persistent hip pain and limp are not uncommon after such procedures, and some authors suggest a major component of this pain is damage to the abductor tendons [1,6,7,12]. Bain and colleagues reported a 40% incidence of persistent trochanteric pain after femoral nailing [1].…”
Section: Introductionmentioning
confidence: 97%